EDUCATION MANAGEMENT MODEL OF DISCIPLINE SANTRI IN ISLAMIC BOARDING SCHOOLS (Study At Modern Boarding Shcool Shalahuddiin Al-Munawwarah) - Barma, Barma Samawi (FITRAH: International Islamic Education Journal, 2019)
Education is a very important factor of human development. Discipline is a compliance in implementing regulations. It must be acknowledged that pesantren have been able to influence the discipline of santri. The purpose of this study is to find out the management model of education in the discipline of santri which includes planning, organizing, implementing and supervising. And to find out the obstacles that faced in Shalahuddiin Al-Munawwarah Islamic Boarding School of applying discipline. This research uses descriptive qualitative research, the data collection by interview, observation, and documentation. In this study, found that the education management model of the santri disciplinary included four aspects, Planning, organizing, implementing and controlling. Planning includes, 1)formulating regulations according to pesantren's vision, mission and objectives, 2)making pesantren regulations, 3)formulating sanctions. Organizing by arranging the duties of administrators from teachers and santri. The implementation are 1)giving guidance, 2)giving motivation, 3)executing, 4)exemplary. The supervising are 1)reports directly, 2)attendance, 3) spying. So, there were found three management models of disciplinary education for santri, 1)a classic organizational model, this model had functions of planning, organizing, implementing and controlling, 2)an authoritarian educational management model, 3) a model of habituation and exemplary. The obstacles faced, 1)there are students who do not want to be disciplined, 2)the lack of support of some santri’s parent, 3)there are some santri who have problems with self-discipline.